Analysis on the Causes of the “Zero Spectators” Phenomenon in Campus Football Matches in China - Chen, Shuqiao (Journal of Social Science and Humanities, 2026)
Based on the context of sports-education integration, this study sorts out the current situation of spectatorship in campus football matches, and deeply explores the causes of the “zero spectators” phenomenon through literature review and semi-structured interviews. The findings show that although China’s campus football competition system is complete and widely covered, the prevalent “zero spectators” phenomenon has become a major constraint restricting its development. Extensive competition organization, single promotion methods, conflicts between match time and teaching/family schedules, insufficient cultivation of football culture, as well as cognitive biases of schools and parents, jointly lead to weak appeal of matches, poor spectator access and low audience participation. In response, it is necessary to change cognition, optimize competition operation and promotion, create a football cultural atmosphere, and improve facilities and evaluation mechanisms, so as to break the “zero spectators” dilemma and promote the high-quality development of campus football.